Critical Thinking Skills Students on Solar System Material - Kurniati, Ilmi; Yuliani, Yuliani; Suyono, Suyono; Mahroini, Zahidah (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
Critical thinking skills are one of the aims of the 21st century. Learning the solar system is one of the science materials that cannot be separated from critical thinking skills. Therefore, research on the students’ initial critical thinking skills is essential after the pandemic. The subjects in this research were Junior High School students. Descriptive methods were used in this research. The data collection instruments used interview methods and research tests—the results of research ability critical thinking students of junior high school in the very low category. The achievement of the interpretation indicator shows a high proportion of 77%. In contrast, the lowest value is found in the analysis indicator, 55%, and the other indicator, like inference, shows 60%. The evaluation and explanation indicators have the same value of about 64%. The research implication is that there is evidence that students’ critical thinking skills still need to be improved, especially in the solar system.